Estudio de factibilidad para la implementación de una empresa de envejecimiento de arroz y su comercialización en la provincia de Loja. - Mendoza Soto, Cosme Arturo (2010)
The urgent necessity to increase the socio-economic development of the county of Loja, makes that this thesis goes focused to execute a project of feasibility for the implementation of a company of aging of rice and its commercialization in the county of Loja. The development of this project began with the market study whose purpose is to determine the demand and offer of the rice for that which a survey was made to 382 consumers that are located in the four cantons: Loja, Bald, Catamayo and Avocados., he/she was also carried out a survey to 198 retailers located in the mentioned cantons. Based on these data you could determine the projection of the demand and offer and consequently the unsatisfied demand that ascended for the year 2009 to 44.274 quintals of rice for family. You proceeded with the elaboration of the commercialization plan taking into account to the price, product, square and distribution channels. You continued to develop the technical study of the project with the determination of the size and localization. Inside the size the installed capacity was calculated (24.000 quintals) and the capacity used year 2009 of 20.400 quintals. The localization was focused in form macro and micro, the exact point of the location of the company to be implanted is the Industrial Park of the city of Loja. As for the engineering of the project he/she shows up the productive process with all their phases, a plan of the physical distribution of the plant is attached. In the financial study he/she shows up the investment that ascends $ 151.118,60 whose financing is based on internal and external sources, it is also calculated the general costs of production with the purpose of ending up knowing the unitary price of sale for quintal of rice that is of for the first year $ 36.15. You continuous to determine the indicators of financial evaluation of the project, as VAN, TIR, B/C, P/R and Analysis of Sensibility what determines that it is advisable the implementation of this company. As for the Administrative Organization, it has been thought of a company of Limited Responsibility, for the favorable conditions that it presents this company type.